Iron fleet : the Great Lakes in World War II - Joachim, George J. (Great Lakes books., 1994)
Iron Fleet focuses on the vital role played by the Great Lakes shipping industry during World War II. In the first book on the subject, George J. Joachim examines how the industry met the unprecedented demand for the shipment of raw materials to meet production quotas during the war, when failure to do so would have had disastrous consequences for the nation's defense effort. In describing the evolution of the Great Lakes shipping industry during World War II, Joachim also explores the use of Great Lakes shipyards for the production of salt water civilian and military vessels, the role of Great Lakes passenger ships in providing vacation opportunities for war workers, and the extensive measures taken to safeguard the Soo Locks and other potential targets from sabotage.